Comparative Efficacy of Maitland’s Mobilization & Mulligan’s Mobilization in Chronic Non-Specific Low Back Pain Among Hospital Ward Nurses- An Interventional Study - Pawar, Vaishnavi; Rayjade, Amrutkuvar (Journal of Neonatal Surgery, 2025)
Introduction: Low back pain is a problem that continues to exert significant strain on the healthcare system. Back injuries were found to be six times more common in nurses than in other health workers. Both acute and chronic lower back pain (LBP) can result from lumbar strains and sprains brought on by stretch injuries to the muscles, ligaments, or tendons in the lower back area. Maitland and Mulligan mobilization techniques are known to be beneficial for persons suffering from low back pain. As a result, there is a need to investigate the effects of Maitland's mobilization and Mulligan’s mobilization for low back pain among hospital working nurses. Methodology: This study examined nurses with non-specific chronic low back pain, aged between 25-45 years who had non-specific chronic low back pain with reduced range of motion, pain and increased disability index. According to study’s criteria, 54 participants were selected for the study and randomly assigned into two groups to receive two different treatments along with Hot Moist Pack and conventional therapy. Group A received SNAG’s Mulligan’s mobilization and Group B received Maitland’s mobilization. The Numerical Pain Rating Scale(NPRS), Bubble Inclinometer and Modified Oswestry Disability Index (MODI) were used as outcome measures. Results: The comparison between the means and S.D of Group A and Group B reveals that both groups experienced improvements, though Group B consistently showed slightly better outcomes across all measured parameters. In terms of pain reduction, Group B had a lower mean NPRS (Numeric Pain Rating Scale) score of 2.67 (±0.62) with a statistically significant p-value of 0.0041. For disability, measured by the MODI (Modified Oswestry Disability Index), Group B with a lower mean score of 10.63 (±3.01) and a significant p-value of 0.0398. Lumbar range of motion also showed improvement in Group B where Lumbar flexion was higher in Group B, with a mean of 69.44° (±8.81) supported by a p-value of 0.0026. Similarly, lumbar extension was greater in Group B, averaging 24.26° (±3.81). the difference was highly significant, with a p-value of 8.44713×10⁻⁵. Overall, Group B demonstrated superior outcomes in pain reduction, disability improvement, and lumbar mobility compared to Group A. Conclusion: The result of study suggests that both Mulligan’s Mobilization and Maitland’s posteroanterior mobilization reduced the symptoms and improved mobility in the patients suffering from chronic non-specific low back pain. Better improvement was shown by Maitland’s group than SNAG group.